Genetic incompatibilities and reduced transmission in chickens may limit the evolution of reassortants between H9N2 and panzootic H5N8 clade 2.3.4.4 avian influenza virus showing high virulence for mammals. Issue 2 (15th October 2020) - Mostafa, Ahmed; Blaurock, Claudia; Scheibner, David; Müller, Christin; Blohm, Ulrike; Schäfer, Alexander; Gischke, Marcel; Salaheldin, Ahmed H; Nooh, Hanaa Z; Ali, Mohamed A; Breithaupt, Angele; Mettenleiter, Thomas C; et al.
Abstract: The unprecedented spread of H5N8- and H9N2-subtype avian influenza virus (AIV) in birds across Asia, Europe, Africa, and North America poses a serious public health threat with a permanent risk of reassortment and the possible emergence of novel virus variants with high virulence in mammals. To gain information on this risk, we studied the potential for reassortment between two contemporary H9N2 and H5N8 viruses. While the replacement of the PB2, PA, and NS genes of highly pathogenic H5N8 by homologous segments from H9N2 produced infectious H5N8 progeny, PB1 and NP of H9N2 were not able to replace the respective segments from H5N8 due to residues outside the packaging region. Furthermore, exchange of the PB2, PA, and NS segments of H5N8 by those of H9N2 increased replication, polymerase activity and interferon antagonism of the H5N8 reassortants in human cells. Notably, H5N8 reassortants carrying the H9N2-subtype PB2 segment and to lesser extent the PA or NS segments showed remarkably increased virulence in mice as indicated by rapid onset of mortality, reduced mean time to death and increased body weight loss. Simultaneously, we observed that in chickens the H5N8 reassortants, particularly with the H9N2 NS segment, demonstrated significantly reduced transmission to co-housed chickens. Together, while the limited capacity for reassortment between co-circulating H9N2 and H5N8 viruses and the reduced bird-to-bird transmission of possible H5N8 reassortants in chickens may limit the evolution of such reassortant viruses, they show a higher replication potential in human cells and increased virulence in mammals.